Corporate Internationalization and Audit Quality - Yiyang Jiang; Weiping Liu (Journal of Frontier in Economic and Management Research, 2025)
As economic globalization deepens, Chinese enterprises are accelerating their internationalization process, making global operations a crucial strategic choice for enhancing competitiveness and achieving sustainable development. Against this backdrop, the impact of internationalization on audit quality has become a significant topic of interest in both academic and professional circles. This study examines the influence mechanism of internationalization on audit quality using Chinese enterprises from 2003 to 2022 as its sample. The findings reveal a significant positive correlation between the degree of internationalization and audit quality, indicating that international operations can effectively enhance audit quality. Robustness tests, including variable substitution and alternative dependent and independent variables, consistently confirm the core conclusions. Further analysis indicates that the moderating effect of foreign direct investment at the regional level significantly amplifies the positive impact of internationalization on audit quality. On one hand, internationalization reduces information transparency and increases financial risks, indirectly boosting audit demand. On the other hand, it enhances audit supply through talent influx and external audit services, ultimately elevating audit quality. Heterogeneity tests reveal that the quality-enhancing effect of internationalization is more pronounced in manufacturing, high-tech, and technology-intensive firms, with eastern and western enterprises outperforming their central counterparts. This study provides theoretical support for the relationship between corporate internationalization strategies and audit quality, offering valuable insights for policymakers seeking to optimize regulatory frameworks.